Case studies to enhance student evaluation : 2015 Central Queensland University : the big red button. - Kinash, Shelley; Naidu, Vishen; Santhanam, Elizabeth; Fleming, Julie; Tulloch, Marian; Tucker, Beatrice; Sid Nair, Chenicheri; Judd, Madelaine-Marie (Office for Learning and Teaching, 2015)
Online student evaluation systems are an opportunity for student engagement and learning improvement. However, they are currently limited by low response rates. Educators tend not to trust them and students describe the activity of filling in multiple surveys as futile. Student feedback processes have largely become academic performance review instruments rather than evaluation and change catalysts. However, there are universities successfully using student evaluation to measure student course engagement and learning development, and then involving students in improving the overall student experience. This document presents a case study from a project designed to fully develop at least six such innovations into case studies. The project pursued the questions: how can we measure student engagement and learning success using student evaluation processes? And how can students contribute to on-going improvement in university learning and teaching? The team drew out a cohesive set of key issues, strategies and recommendations to disseminate to the higher education sector through a symposium. This paper focuses on Central Queensland University (CQUniversity), which has adopted a variety of methods to encourage student feedback through online course evaluations. This has seen an increase in student response rates. These include, integrating course evaluations into the Moodle Learning Management System (LMS); providing incentives; and delivering online prompts including pop-ups in the LMS sites and email reminders.